Tibåt Mårqe: A New Edition with English Translation - Ṭal, Avraham (Religions, 2020)
This contribution presents a short introduction to the new edition of Tibåt Mårqe. The oldest manuscript of Tibåt Mårqe dates from the 14th century but only fragments of it are preserved. Previous editors of Tibåt Mårqe included those fragments in their editions which, by necessity, were based on a later, less reliable version of this collection of Samaritan midrashim. The recent discovery of large portions of the 14th century manuscript of Tibåt Mårqe in the National Library of Russia in St. Petersburg made it possible for me to fill most of the gaps. The new edition presented here is therefore based on an improved instrument of research in the domain of Samaritan culture.